Mutation mismatch repair gene deletions in diffuse large B-cell lymphoma. Issue 5 (May 2013) - Couronné, Lucile; Ruminy, Philippe; Waultier-Rascalou, Agathe; Rainville, Vinciane; Cornic, Marie; Picquenot, Jean-Michel; Figeac, Martin; Bastard, Christian; Tilly, Hervé; Jardin, Fabrice
Abstract To further unravel the molecular pathogenesis of diffuse large B-cell lymphoma (DLBCL), we performed high-resolution comparative genomic hybridization on lymph node biopsies from 70 patients. With this strategy, we identified microdeletions of genes involved in the mutation mismatch repair (MMR) pathway in two samples. The first patient presented with a homozygous deletion of MSH2–MSH6 due to duplication of an unbalanced pericentric inversion of chromosome 2. The other case showed a PMS2 heterozygous deletion. PMS2 and MSH2–MSH6 abnormalities, respectively, resulted in a decrease and complete loss of gene expression. However, unlike tumors associated with the hereditary non-polyposis colorectal cancer syndrome or immunodeficiency-related lymphomas, no microsatellite instability was detected. Mutational profiles revealed especially in one patient an aberrant hypermutation without a clear activation-induced cytidine deaminase signature, indicating a breakdown of the high-fidelity repair in favor of the error-prone repair pathway. Our findings suggest that in a rare subset of patients, inactivation of the genes of the MMR pathway is likely an important step in the molecular pathogenesis of DLBCL and does not involve the same molecular mechanisms as other common neoplasms with MMR deficiency.